The cameraman's revenge and other fantastic tales (1912-1958) - Starewicz, Ladislaw (Chatsworth, CA : Image Entertainment, 2000)
Six animated works produced by Starewicz in Moscow and Paris between the years 1912 and 1958. As the world's first great puppet and stop-motion model animator, Starewicz was best known for his insect stories. Starewicz's grasshoppers, dogs, frogs, dolls, and other creatures portray heroics and follies with an exuberance of humor and invention. ##- The cameraman's revenge = Mest' kinematografich-eskogo operatora / produced by Khanzhonkov Co., 1912 (13:00) ##- The insects' Christmas / produced by Khanzhonkov Co., 1913 (7:00) ##- Frogland : The frogs who wanted a king = Les grenouilles qui demandent un roi, 1922 (9:00) ##- Voice of the nightingale = La voix du rossignol, 1923 (13:00) ##- The mascot = Fetiche mascotte / produced by Gelmafilm, 1933 (26:00) ##- Carrousel boréal = Winter carousel / un film de L. Starewitch, 1958 (12:00).
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Starewicz, Ladislaw